The effect of emotional communication on infants' distinct prosocial behaviors. Issue 4 (14th June 2020) - Walle, Eric A.; Reschke, Peter J.; Main, Alexandra; Shannon, Roisin M.
Abstract: Discrete emotions convey distinct relational meanings that inform the response of a social partner, such as how to help. Although prosocial behaviors can take different forms and are observed in a variety of contexts across development, distinct forms of helping are often studied in forced‐choice settings in limited emotional contexts. This study examined the prevalence of three prosocial behaviors (instrumental helping, comforting, and indirect helping) by 16‐, 19‐, and 24‐month‐old infants in response to situations involving an experimenter reacting emotionally (anger, disgust, fear, sadness, and joy) to an event (a broken toy; an unknown object). Instrumental helping was more prevalent in response to sadness than fear, anger, disgust, and joy, with instrumental helping in joy contexts emerging at 24 months. Conversely, comforting was largely absent in joy and disgust contexts in comparison to the other emotional contexts and increased overall with age. Indirect helping was rarely observed in response to disgust and joy and was most frequent in response to sadness. Furthermore, both 24‐ and 19‐month‐olds were more likely to engage in indirect helping compared with 16‐month‐olds. This study supports the view that infant prosocial behavior is influenced by emotional cues and that distinct forms of helping emerge gradually in infancy.